Travel Literature in Islamic History and Its Enrichment of Civilizational Communication: A Descriptive Study - Al Shehhi, Khawla (Al-Adab Journal, 2025)
Travel literature has a significant role in enriching cultural communication through the transmission of knowledge, news, characteristics, and other observations made by travelers during their journeys. Their writings and records encompassed many geographical features and societal traits, focusing on these aspects and evidences, which in turn contributed to fostering cultural communication among Muslims and with other nations and peoples encountered by Muslim travelers. The expansion of the state after the Islamic conquests allowed travelers to explore the territories under their control, becoming part of their state. They delved intellectually into various regions, observing and researching, adapting to each place and time, documenting their observations, mapping routes, and organizing postal systems. Describing regions and attending to them became part of the news of conquests and battles.Several factors contributed to the flourishing of travel literature throughout Islamic eras, including religious motivations such as pilgrimages and Umrah, Islamic conquests, or scientific and educational purposes to gain knowledge from renowned centers of various sciences such as jurisprudence, medicine, and engineering. Political motivations included delegations and embassies sent by kings and rulers to their counterparts in other states to strengthen relations. Additionally, there were tourism and cultural motivations driven by the desire to explore the world and the globe, travel for its own sake, and the love of movement. Moreover, trade journeys, which expanded among Muslims during the medieval period, also played a role. Travelers provided descriptions of peoples, their customs, traditions, morals, and attire.The study concluded that Muslim travelers had deep knowledge of the social, religious, and cultural lifestyles of the peoples they visited, enabling them to interact and engage with others through discussions, debates, and scholarly gatherings. This significantly deepened the cultural communication between Muslim travelers and others.